Highly selective and scalable CO2 to CO - Electrolysis using coral-nanostructured Ag catalysts in zero-gap configuration. (October 2020) - Lee, Woong Hee; Ko, Young-Jin; Choi, Yongjun; Lee, Si Young; Choi, Chang Hyuck; Hwang, Yun Jeong; Min, Byoung Koun; Strasser, Peter; Oh, Hyung-Suk
Abstract: The direct electroreduction of CO2 to pure CO streams has attracted much attention for both academic research and industrial polymer synthesis development. Here, we explore catalytically very active, coral-structured Ag catalyst for the generation of pure CO from CO2 -feeds in lab-bench scale zero-gap CO2 electrolyzer. Coral-shaped Ag electrodes achieved CO partial current densities of up to 312 mA cm −2, EECO of 38%, and FECO clearly above 90%. In-situ/operando X-ray Absorption Spectroscopy revealed the sustained presence of Ag + subsurface species, whose local electronic field effects constitute likely molecular origins of the favorable experimental kinetics and selectivity. In addition, we show how electrode flooding in zero-gap CO2 electrolyzer compromises efficient CO2 mass transfer. Our studies highlight the need for a concomitant consideration of factors related to intrinsic catalytic activity of the active phase, its porous structure and its hydrophilicity/phobicity to achieve a sustained high product yield in AEM zero-gap electrolyzer. Graphical abstract: Coral-shaped Ag for electrochemical CO 2 reduction was measured for catalytic activity in zero-gap CO2 flow electrolyzer and in-situ/operando X-ray absorption spectroscopy under real device conditions. Ag coral achieved a high current density and Faradaic efficiency for CO owing to the porous structure and Cl-doped-Ag coral surface with abundant defects. Furthermore, the role of electrode flooding owing to increased hydrophilicity is discussed. Image 1 Highlights: Coral-structured Ag electrode was prepared for generation of CO in lab-bench scale zero-gap CO2 electrolyzer. Ag coral electrodes achieved CO partial current densities of up to 312 mA cm −2 and FECO above 90%. Ag electronic structure was observed using operando X-ray absorption spectroscopy under real device conditions. Cl-doped-Ag coral possess enhanced negative electric fields, leading low overpotential for CO2 reduction to CO. Hydrophobicity of the electrode was important to prevent the flooding by improving mass transfer of CO2 .